The prevalence of dementia in rural Tanzania: a cross‐sectional community‐based study. (20th September 2012) - Longdon, Anna R.; Paddick, Stella‐Maria; Kisoli, Aloyce; Dotchin, Catherine; Gray, William K.; Dewhurst, Felicity; Chaote, Paul; Teodorczuk, Andrew; Dewhurst, Matthew; Jusabani, Ahmed M; Walker, Richard
<x xml:space="preserve">Abstract</x> Objectives Despite the growing burden of dementia in low‐income countries, there are few previous data on the prevalence of dementia in sub‐Saharan Africa. The aim of this study was to estimate the prevalence of dementia in those who are 70 years and older in the rural Hai District of Tanzania. Methods This was a two‐phase cross‐sectional survey. Using census data, we screened individuals aged 70 years and older from six rural villages using the Community Screening Instrument for Dementia in Phase I. In Phase II, a stratified sample of those identified in Phase I were clinically assessed using the DSM‐IV criteria. Results Of 1198 people who fulfilled the inclusion criteria, 184 screened positive for probable dementia, and 104 screened positive for possible dementia using the Community Screening Instrument for Dementia. During clinical assessment in Phase II, 78 cases of dementia were identified according to the DSM‐IV criteria. The age‐standardised prevalence of dementia was 6.4% (95% confidence interval: 4.9 to 7.9). Prevalence rates increased significantly with increasing age. Conclusions The prevalence of dementia in this rural Tanzanian population is similar to that reported in high‐income countries. Dementia is likely to become a significant health burden in this population as demographic transition continues. Further research on risk factors for dementia in sub‐Saharan Africa is needed to inform policy makers and plan local health services. Copyright © 2012 John Wiley & Sons, Ltd.